TI_GERICHTE 12.2016.132 vom 23. Oktober 2017 , Contratto di locazione, protrazione, assunzione nuove prove in appello - TI Tribunale d'appello (2017)
Contratto di locazione, protrazione, assunzione nuove prove in appello